ANALISIS PEMETAAN SISTEM BLOK AIR PADA PETANI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DI KABUPATEN SUMBAWA BARAT - NOVAL, ARDIAN; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; UMAR, UMAR (GANEC SWARA, 2023)
Water resources are one of the natural assets that are very important in supporting human life and various economic sectors. The aim of this research is to identify the use of technology and innovation in the management and distribution of water distribution mapping to farmers carried out by the West Sumbawa Regency Public Works and Spatial Planning Service. The method used in this research is qualitative method. The results of this research are, 1) The West Sumbawa Regency Public Works and Spatial Planning Service's water distribution mapping program for farmers has been going well, not only is the government itself working but farmers are also playing an active role in the program. This can be seen in the sense of togetherness through mutual cooperation and the results can improve the farmer's own economy. 2) Factors that influence the distribution of water distribution mapping are the climate, or whether the agricultural area is wet or dry. 3) The Department of Public Works and Spatial Planning utilizes a collaboration system with other parties in developing technology and innovation in the management and distribution of water distribution mapping in the form of creating programs for the application of new technology in water resource management